Acesso do Estudante com Deficiência Visual ao Currículo nas Universidades na Perspectiva da Escola Justa - Costa, José Aparecido da (2021)
This research investigates aspects related to the access of visually impaired students to the curriculum in universities from the perspective of fair school. In such a context, its main objective is to ascertain, if the mentioned students, observing the limits of the legislation that deals with access and still, considering the resources linked to Assistive Technology, they enjoy the conditions that can guarantee access to the curriculum in its dimensions, guaranteeing thus, the effective participation in the courses attended in the university environment, observing principles such as equality, equal opportunities, distributive justice, as they appear in the constitution of fair school. In this sense, the survey brings the main tools linked to assistive technology. It should be emphasized that in the case of those inserted in the computational field, these resources are limited to those coming from open source. As for the research methodology, it is of a qualitative nature, characterized as descriptive-analytical, encompassing semi-structured and primary sources, being of bibliographic and documentary basis. It is inspired by the historical-cultural approach and had the participation of 6 visually impaired students with (blindness and low vision), from public and private universities. With regard to the results provided in the thesis, among others, the following are highlighted: the broad set of laws on the subject and about thematic to a certain extent. The profusion of resources available in the area of computational technology and the diminished use by the mentioned students. The results also reveal the decline in the use of the Braille System and the autonomy of university students in the development of the evaluation process. Finally, proposals are made to ensure that the gaps identified through research are overcome. Keywords: access; visually impaired students; fair school.